2016
DOI: 10.22260/isarc2016/0035
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Technology for Construction Safety: A Feasibility Study

Abstract: A construction site is a harsh environment demanding entire human senses and attention, even for regular scheduled tasks. Many accidents occur on construction sites because of inability of workers to identify hazards and make timely decisions. To understand why some hazards go unseen, it is crucial to study how workers perceive the site. The objective of this research is to leverage eye-tracking technology to study workers' gazing pattern in a construction environment. A real picture from an active constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…These devices allow the capture of the highest-quality data by restricting the participant’s head movement, although they are less realistic and natural. The saccade resolution of a remote eye tracker fitted with a head-supporting tower is two to five times greater than that of a remote/head-free eye tracker [ 16 ]. However, the restrictive setting of head-supporting towers limits their use for dynamic environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These devices allow the capture of the highest-quality data by restricting the participant’s head movement, although they are less realistic and natural. The saccade resolution of a remote eye tracker fitted with a head-supporting tower is two to five times greater than that of a remote/head-free eye tracker [ 16 ]. However, the restrictive setting of head-supporting towers limits their use for dynamic environments.…”
Section: Resultsmentioning
confidence: 99%
“…A good tool for measuring eye movement and eye position information is by using an eye tracking device. This unique tool allows eye movement information to be recorded, which can help to assess an individual’s mental state, to understand cognitive processing and behaviour, and to interpret individuals’ responses to different visual stimuli [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such experimentation can thus lend significant more data than traditional eye-tracking experimentation and facilitate novel workflows. While it is true that data collected in this way is of less ecological validity than that collected in situ, initial studies have shown that viewing patterns captured in virtual scenes may approximate those captured in real scenes well [50]. [4].…”
Section: Exploring How Workers Detect and Assess Hazardous Situationsmentioning
confidence: 99%
“…Examples of technology-oriented solutions include efforts such as sharing safety knowledge using a mobile device [9], real-time data collection and visualization technology for construction safety [10] and [11], safety assessment of construction site using geographic information systems (GIS) [12], visionbased recognition of construction equipment and hazard detection [13], game technology combined with visualizing safety assessment [14], autonomous jobsite safety proximity [15], location-aware sensing technology to determine a worker's safety situation regarding proximity to dangers [16], use of digital models to enhance construction safety [17], enhancing hazard recognition with augmented virtually [18], and the applications of building information modeling (BIM) to investigate potential fall hazards [19]. Among these studies few of them have investigated the application of eye-tracking technology in construction safety [20]. Dzeng et al [21] used an eye-tracking system to compare how the experienced and novice workers pay attention to the obvious and unobvious hazards.…”
Section: Introductionmentioning
confidence: 99%